Hot-headed peckers: thermographic changes during aggression among juvenile pheasants (Phasianus colchicus) - Knoch, Sophia; Whiteside, Mark; Madden, Joah; Rose, Paul; Fawcett, Tim (Dryad, 2021)
In group-living vertebrates, dominance status often covaries with
physiological measurements (e.g. glucocorticoid levels), but it is unclear
how dominance is linked to dynamic changes in physiological state over a
shorter, behavioural timescale. In this observational study, we recorded
spontaneous aggression among captive juvenile pheasants (Phasianus
colchicus) alongside infrared thermographic measurements of their external
temperature, a non-invasive technique previously used to examine stress
responses in non-social contexts, where peripheral blood is redirected
towards the body core. We found low but highly significant repeatability
in maximum head temperature, suggesting individually consistent thermal
profiles, and some indication of lower head temperatures in more active
behavioural states (e.g. walking compared to resting). These individual
differences were partly associated with sex, females being cooler on
average than males, but unrelated to body size. During pairwise aggressive
encounters, we observed a non-monotonic temperature change, with head
temperature dropping rapidly immediately prior to an attack and increasing
rapidly afterwards, before returning to baseline levels. This nonlinear
pattern was similar for birds in aggressor and recipient roles, but
aggressors were slightly hotter on average. Our findings show that
aggressive interactions induce rapid temperature changes in dominants and
subordinates alike, and highlight infrared thermography as a promising
tool for investigating the physiological basis of pecking orders in
galliforms.
Thermographic, behavioural and morphometric measurements collected from
captive juvenile pheasants. All processing done within accompanying R
script.
Variables are defined in the accompanying ReadMe files. Missing values are
coded as NA.
Keywords: Aggression; dominance hierarchy; infrared thermography; pecking order; social defeat; stress-induced hyperthermia